Enzymatic hydrolysis of N.gaditana sp for bioactive peptide production - Md Saleh, Nur Izzati; Wan Ab. Karim Ghani, Wan Azlina; Harun, Mohd Razif; Mustapa Kamal, Siti Mazlina (2017)
Microalgae Nannochloropsis gaditana (N.gaditana sp) was used as a starting material to produce microalgae protein hydrolysate (MPH) by protease enzyme. The effect of pH, temperature, enzyme concentration and substrate concentration on the degree hydrolysis (DH) were investigated. The screening of enzymatic hydrolysis reaction time was conducted from 1 hr and up to 48 hours. The enzymatic hydrolysis reactions were conducted for 24 hours for all set experiments based on the screening time. The maximum cleavage of peptide bonds occurred was found at pH 8 (DH=41.69%), temperature 55°C (DH=42.53%), enzyme concentration 0.3 mg/L (DH=43.96%) and substrate concentration 2 g/L (DH=58.70%). These results demonstrated that N.gaditana sp is rich in bioactive peptide which has the capability to be an antioxidant.